Studies on bactericidal efficacy of pumpkin (Cucurbita moschata Duchesne) peel - Ahmed, Qamar Uddin; Helaluddin, Abul Bashar Mohammed; Khan Chowdhury, Ahmed Jalal (Coastal Life Medicine Media co. Limited, 2014)
Objective: To explore the in vitro antibacterial potential of the peel of Cucurbita moschata Duchesne (tropical pumpkin) (C. moschata) against human pathogenic bacteria. Methods: In the present study, dichloromethane (DCM), methanol (MEOH) and aqueous extracts of C. moschata peel were examined for in vitro antibacterial potency against eight bacterial strains i.e. Bacillus cereus, Burkholderia cepacia, Escherichia coli, Enterococcus faecalis, Staphyloccocus aureus, Pseudomonas aerugenosa, Vibrio alginolyticus, Vibrio parahaemolyticus using Kirby- Bauer disk diffusion susceptibility and broth micro-dilution methods. Results: DCM extract of pumpkin peel exhibited the maximum zone of inhibition against Staphyloccocus aureus (21 mm) whereas aqueous extract of pumpkin peel revealed the least zone aofg aininhsitb iPtisoenu daogmaionnsta sE sacehreurgicehnioas ac o(l1i9 ( 8m mmm). ).B MroEtOhH m eixctrroa-cdt igluavtieo nm amxeimthuomd szhoonwe eodf imnihnibimituiomn imnihniibmituomry bcaocntceernictirdaatilo cno fnocre tnhtera tDioCnMs ewxetrraec at lasgo adinestet rBmuinrkehdo tlod ekrinao wce pthaec inaa atut r6e. 2o5f malgl /emxLtr.a Tchtse. DCM and MEOH extracts exhibited bactericidal nature to all bacterial strains except for the Vibrio alginolyticus. The minimum bactericidal concentrations values exhibited bactericidal nature reaxntrgaicntgs forfo mC. 3m.1o2s cmhga/tma Lp etoe l 1r0e0v.0e0a lmedg /tmhaLt. tThhee D sCcMre eexntirnagc to pf oasnsteismsiecdr ogboioadl parnotpimeritcireosb oiaf l deiffffiecraecnyt compared to MEOH and aqueous extracts. Conclusions: Peel of C. moschata possesses antibacterial compounds and could be potential source for a new class of antibiotics.